Integrating Vernacular Architecture into Science Education: Ethnoscience Analysis of Dayak Traditional Houses for Context-Based Learning - Nurussaniah Nurussaniah (Program Studi Pendidikan Fisika, Fakultas Pendidikan MIPA & Teknologi, Universitas PGRI Pontianak, 2025)
Ethnoscience-based approaches offer a promising pathway for making science education more culturally relevant and effective in diverse Indonesian school contexts. This paper presents a systematic ethnoscience analysis of Dayak traditional houses (rumah betang) from West and Central Kalimantan and maps the embedded scientific knowledge to Indonesian national science curriculum standards (Kurikulum Merdeka, 2022) for Grades 4–9. Using a qualitative research design combining ethnographic observation, documentary analysis, and curriculum mapping, the study identified 23 distinct scientific concepts across six thematic domains material science, thermal physics, biodiversity and ecology, hydrology, structural mechanics, and sustainability embedded in the design, construction materials, and spatial logic of the rumah betang. Six context-based learning (CBL) scenarios are developed from these findings to provide actionable pedagogical guidance for science teachers in Kalimantan. The paper argues that vernacular architecture constitutes a 'master context' for ethnoscience-based science education: a single, culturally resonant real-world situation capable of anchoring learning across multiple science topics and grade levels. Implications for teacher professional development and curriculum policy in Indonesia are discussed.